Expansion of Lymphocytes from Prostatic Adenocarcinoma and Adjacent Nonmalignant Tissue. (16th June 2022) - Nguyen, Linh T.; Lo, Charlotte S.; Fyrsta, Michael; Nie, Jessica; Yam, Jennifer Y.; Yen, Pei-Hua; Le, Michael X.; Hersey, Karen; Kenk, Miran; Crumbaker, Megan; Fleshner, Neil; Kulkarni, Girish; et al.
Abstract : Background . The evaluation of tumour-infiltrating lymphocytes (TILs) in solid malignancies has yielded insights into immune regulation within the tumour microenvironment and has also led to the development and optimisation of adoptive T cell therapies. Objectives . This study examined the in vitro expansion of TILs from prostate adenocarcinoma, as a preliminary step to evaluate the potential of TILs for adoptive T cell therapy. Design, Setting, and Participants . Malignant and adjacent nonmalignant tissues were obtained from fifteen men undergoing radical prostatectomy. Interventions . There were no study interventions. Outcome Measurements and Statistical Analysis . Expanded cells were analysed by flow cytometry, and the data was assessed for associations between cell subpopulations and expansion rate. Results . Tumour-infiltrating lymphocytes could be expanded to numbers that would be needed to generate a therapeutic infusion product from nine of 15 malignant specimens (60%). The CD4 + T cells predominated over CD8 + T cells (median 56.8% CD4 +, 30.0% CD8 + ), and furthermore, faster TIL expansion was associated with a higher proportion of CD4 + T cells (median 69.8% in faster-growing cultures; 36.8% in slower-growing cultures). A higher proportion of CD3 − CD56 + cells versus CD3 + cells was associated with slower TIL expansion in cultures from malignant specimens (median 13.3% in slower-growing cultures versus 2.05% in faster-growing cultures), but not from nonmalignant specimens. Conclusions . The expansion of TILs for potential therapeutic use is feasible. Our findings also indicate that further examination of TILs from prostate adenocarcinomas may yield insights into mechanisms of regulation of T cells within the tumour microenvironment. Further research is required to evaluate their therapeutic potential.